Exploring organisational hybridity from a learning perspective. Issue 4 (9th October 2017) - Knutsson, Hans; Thomasson, Anna
Abstract : Purpose: The purpose of this paper is to explore if the application of a framework building on organisational learning focusing on organisational processes can increase our understanding of how hybrid organisation develops over time and why they fail to live up to external expectations. Design/methodology/approach: The aim of this study is descriptive and explorative. It is accordingly designed as a qualitatively oriented case study. To capture the process of forming and developing hybrid organisations, the study takes a longitudinal approach. The case chosen for the study is a municipally owned company in Sweden providing waste management services. The study revolves around empirical data gathered in official documents and in face-to-face interviews. All the data concern the time span between 2004 and 2016. Findings: The analysis of the case studied provides us with insights into how hybridity manifests itself in mind-set and processes. There is a need for individuals within and around the organisation to be aware of and accept new goals and strategies to change their behaviour accordingly. The result of this study thus shows that contrary to findings in previous research on hybrid organisations, merely changing the structure of the organisation is not sufficient. Instead, learning is key to the development of hybridity and to overcome goal incongruence and conflicts of interest in hybrid organisations. However, this takes time and is likely to be dependent on individuals' willingness to accept and adapt these new strategies and goals. Research limitations/implications: The result of this study is based on one single case study in one specific hybrid context. No empirical generalisation is aspired to. Instead, the aim has been to – through an explorative approach – make an analytical contribution to the knowledge about hybrid organisations. Further studies are thus necessary to deepen the understanding of the hybrid context and the situations under which hybrid organisations operate and develop. Practical implications: Based on the result from this study, it seems that an organisation needs to learn how to be a hybrid organisation. There are no isolated structural solutions that can create a hybrid organisation other than in a formal sense. New ways to exploit organisational resources and the hybrid context are necessary to find new and innovative ways of how to use the hybrid context in a way that improves service sector delivery. Originality/value: Predominately, research on hybrid organisations has until recently been working with the premise that hybrids are not a breed of its own but a mix of two or several ideal types. Consequently, the result from this type of research has often landed in a conclusion regarding the complexity of combining what often is considered contradictory and conflicting goals. In this paper, a different and novel approach is taken. The paper illustrates how hybrid organisations develop over time, and it suggests that hybridity manifests itself in mindset and processes. The main contribution is an exploration and illustration of how organisational learning may be considered as the missing link between the structural orientation of previous explanations of hybrid organisations and the organisational property of hybridity. Hybridity is the result of exposure to, acceptance of and adaptation to new goals and strategies and expresses itself in "hybrid behaviour".